Efektivitas Pembelajaran Pak Berbantuan Metode CTL Fase D Kelas VII Di SMP Yos Sudarso Indramayu (International Forum of Researchers and Lecturers, 2023)
Education has a very important and fundamental role for the future generations of a nation and state. Critical reasoning skills are very important for students to have in learning. Based on the results of observations and interviews conducted with Yos Sudarso Indramayu Junior High School teachers, information was obtained that students were passive in participating in learning, this was evident in the low interest in asking questions, arguing, and taking initiative during learning. This research aims to offer CTL methods in order to create more interactive learning so that students can bring learning activities to life, analyze the material to see its integrity with their daily lives. This research uses a kunatitaif approach with the application of experiments. The subjects of this study were seventh grade students of SMP Yos Sudarso Indramayu. Data collection techniques using observation / observation and student learning outcomes test.